Experimental research and numerical simulation of gel fuel ignition by a hot particle; Fuel; Vol. 291 - Glushkov D. O. Dmitry Olegovich; Kosintsev A. G. Andrey Georgievich; Kuznetsov G. V. Geny Vladimirovich; Vysokomorny (Vysokomorniy) V. S. Vladimir Sergeevich (2021, 2021)
Title screen